2012
DOI: 10.1371/journal.pone.0043293
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis SepF Binds to the C-Terminus of FtsZ

Abstract: Bacterial cell division is mediated by a multi-protein machine known as the “divisome”, which assembles at the site of cell division. Formation of the divisome starts with the polymerization of the tubulin-like protein FtsZ into a ring, the Z-ring. Z-ring formation is under tight control to ensure bacteria divide at the right time and place. Several proteins bind to the Z-ring to mediate its membrane association and persistence throughout the division process. A conserved stretch of amino acids at the C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 34 publications
1
42
0
4
Order By: Relevance
“…We further observed that the conserved lysine residue (190K) of SepF MTB and the C terminus of FtsZ are important for the SepF-FtsZ interaction in mycobacteria. SepF also binds to the C terminus of FtsZ in B. subtilis (Kró l et al, 2012). P372 present in the C terminus of B. subtilis FtsZ is required for interaction with SepF.…”
Section: Sepf Interacts With Ftsz and Murg In Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…We further observed that the conserved lysine residue (190K) of SepF MTB and the C terminus of FtsZ are important for the SepF-FtsZ interaction in mycobacteria. SepF also binds to the C terminus of FtsZ in B. subtilis (Kró l et al, 2012). P372 present in the C terminus of B. subtilis FtsZ is required for interaction with SepF.…”
Section: Sepf Interacts With Ftsz and Murg In Mycobacteriamentioning
confidence: 99%
“…In addition to FtsA, the repertoire of B. subtilis FtsZ-interacting proteins includes SepF, ZapA and ZapB. SepF binds to the C terminus of FtsZ and is required for proper septum formation (Gündogdu et al, 2011;Ishikawa et al, 2006;Kró l et al, 2012). It can complement for the lack of FtsA.…”
Section: Introductionmentioning
confidence: 99%
“…SepF binds directly to the C-terminal domain of FtsZ (6,16). However, the protein has no apparent homology to proteins of known function and the amino acid sequence does not indicate a clear docking site for FtsZ.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, SepF can bind the CTT of either B. subtilis or E. coli FtsZ, indicating that the SepF-FtsZ interaction is dependent on the secondary and tertiary structure of the FtsZ CTT rather than specific amino acid residues (Fig. 1B) (104). Electron micrographs of purified SepF show large regular ring-like structures (76).…”
Section: Sepfmentioning
confidence: 98%